2002
DOI: 10.1113/eph8702372
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Response to Incremental Exercise in Endurance‐Trained Athletes: Influence of Heart Rate, Contractility and the Frank‐Starling Effect

Abstract: Recent evidence indicates that endurance-trained athletes are able to increase their stroke volume (SV) throughout incremental upright exercise, probably due to a progressively greater effect of the Frank-Starling mechanism. This is contrary to the widely held belief that SV reaches a plateau at a submaximal heart rate (irrespective of fitness level), owing to a limitation in the time for diastolic filling. The purpose of this investigation was to evaluate whether endurance-trained athletes rely on a progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 29 publications
(67 reference statements)
3
40
0
1
Order By: Relevance
“…Exercise was performed on a semisupine cycle ergometer, and this will lead to an altered before and after load response during exercise, changing the differential contribution of HR and stroke volume to enhance cardiac output (47). However, our group and others have shown significant stroke volume increase also during supine exercise by using cardiac magnetic resonance imaging (23,36), and a comparative study in children between upright and supine CPET has additionally found good correlation of parameters (29).…”
Section: Methodology Limitationsmentioning
confidence: 99%
“…Exercise was performed on a semisupine cycle ergometer, and this will lead to an altered before and after load response during exercise, changing the differential contribution of HR and stroke volume to enhance cardiac output (47). However, our group and others have shown significant stroke volume increase also during supine exercise by using cardiac magnetic resonance imaging (23,36), and a comparative study in children between upright and supine CPET has additionally found good correlation of parameters (29).…”
Section: Methodology Limitationsmentioning
confidence: 99%
“…Beim Menschen zeigen neuere Untersuchungen, dass Ausdauerbelastung zu signifikant größeren Schlagvolumina und enddiastolischen Volumina führten, als Sportarten mit Kurzzeitbelastung (Di Bello et al 1996, Warburton et al 2002 …”
Section: Sv (Ml)unclassified
“…Isometric exercise causes central cardiac and hemodynamic responses different from those of endurance exercise. 13 Compared with the volume overload imposed by moderate endurance exercise, isometric exercise increases total peripheral resistance (1 component of E a ), causing a disproportionate increase in blood pressure and heart rate and imposing or increasing the LV pressure overload. 14 As a consequence, end-systolic pressure increases.…”
Section: Resting Conditions or Load Challengesmentioning
confidence: 99%